Integrative taxonomic revision of Campylocia (mayflies: Ephemeroptera, Euthyplociidae). Issue 6 (2nd November 2017) - GonÇalves, InÊs C.; Takiya, Daniela M.; Salles, Frederico F.; Peters, Janice G.; Nessimian, Jorge L.
Abstract : A morphological comparison of type and non-type material of species of Campylocia, including their junior synonyms, was conducted, in addition to neighbour joining based on K2P distances and Bayesian inference analyses of 376 bp of the mitochondrial gene cytochrome oxidase I (COI) of recently collected specimens. Results revealed the lack of distinguishing characters between C. bocainensis and C. dochmia supported by the molecular analysis, where the overlap of intra- and interspecific genetic divergences suggested genetic flow among individuals. Campylocia burmeisteri is revalidated as a senior synonym of Brazilian south-eastern species C. bocainensis and C. dochmia and of E. guntheri, formerly a synonym of C. anceps . Campylocia burmeisteri is redescribed based on material from its type-locality, Nova Friburgo, Rio de Janeiro State. Two new species, C. demoulini sp. nov. and C. araca sp. nov., are described from the Amazon rain forest and a third species, C. orosi sp. nov., is described from Costa Rica. Possible cryptic species and the utility of egg morphology in the taxonomy of Campylocia are discussed for the first time for the genus. A key to the identification of adult stages of Campylocia is provided based on male genitalia and egg morphologyhttp://zoobank.org/urn:lsid:zoobank.org:pub:6779DC2C-DB98-41DF-8C52-FF97366AAF7A